Contemporary Jewish communities in three European cities: challenges of integration, acculturation and ethnic identity - Lev Ari, Lilakh (De Gruyter Oldenbourg, 2022)
Contemporary Jewish identity, integration and acculturation in Europe has become an urgent topic in view of the current wave of antisemitism and reliable research on the present state of Jewish identity is scarce. Lilach Lev Ari has chosen three ethnically diverse communities - Paris, Brussels, and Antwerp - that can shed a light on the identity and acculturation of the Jewish minority in Europe. To understand patterns of social integration of native-born and immigrant Jews in the three host societies she applies the correlational quantitative method and has conducted semi-structured interviews. The study can promote further understanding of Jewish continuity within the non-Jewish host societies in a situation, when there is a concern about the resilience and strength of the Jewish communities vis-à-vis new waves of antisemitism